Reliability and Validity Study on Work Safety Culture Questionnaire (WSCQ) among Government Office Worker using Information Motivation and Behavior (IMB) Model - Odu, Josiah Oluwaseun (IIUM Medical Journal Malaysia, 2023)
INTRODUCTION: The Workplace Safety Culture Questionnaire (WSCQ) was developed to assess the level of knowledge, attitudes and practices on Workplace Safety Culture (WSC) among public sector office workers in Nigeria. The main objective of this study was to determine the validity and reliability of the new Workplace Safety Culture Questionnaire (WSCQ) using the Information Motivation and Behavior (IMB) model. MATERIALS AND METHODS: The WSCQ questionnaire was completed twice by the respondents themselves, with an interval of ten days between sessions, to assess the accuracy of the initial results with the retest. This study involved 44 participants. RESULTS: Cronbach’s alpha showed significant item consistency for each construct in the second pilot study. The information construct (Cronbach’s α=0.929 and minimum corrected item-total correlation (CITC)=0.399). The motivation construct (Cronbach’s α=0.932 and minimum corrected item-total correlation (CITC)=0.450). The behavior construct (Cronbach’s α=0.812 and minimum corrected item-total correlation (CITC)= 0.401). In test-retest reliability, Cohen’s kappa coefficient for construct of information for all items was almost 70% between (kappa k=0.689-1000, p<0.001). The intraclass correlation coefficient (ICC) for the construct of motivation for all items is 90% between (ICC=0.810-1000, p><0.001) and (kappa k=0.944-1000, p><0.001) for the construct of behavior was 71% for all items. CONCLUSION: This study introduces the WSCQ using the IMB model among public sector office workers as the first official validation of the WSCQ.>